Age-related changes in plasma levels of BDNF in Down syndrome patients - Licastro Federico; Galliera Emanuela; Dogliotti Giada; Corsi Massimiliano M (Immunity & Ageing, 2010)
Abstract Background The prevalence of coronary artery diseases is low among Down Syndrome (DS) patients and they rarely die of atherosclerotic complications. Histopathological investigations showed no increase in atherosclerosis, or even a total lack of atherosclerotic changes, in DS Aim The aim of our study is to investigate the relationship between age and brain-derived neurotrophic factor (BDNF) levels in Down Syndrome (DS). Subjects and methods Three groups of DS patients were studied: the first consisted of 23 children (age 2-14 years); the second of 14 adults (age 20-50 years), the third group of 13 elderly persons (>60 years) and a controls group of 20 healthy patients (age 15-60 years). The analytes of interest were quantified using a biochip array analyzer (Evidence®, Randox Ltd., Crumlin, UK). Results Plasma BDNF was higher in DS patients than in controls and there was a significant age-related increase. Serum levels of IL-6 and MCP-1 were also higher in DS children and adults, but not in older patients, than in healthy control. High levels of circulating BDNF may protect DS patients from the clinical complications of atherosclerosis. However, the striking drop in peripheral BDNF levels with age might predispose these patients to clinical manifestations of dementia in later life.